Oor eksegese en metodes : die reëls van die spel - De Villiers, Gerda (Old Testament essays, 2006)
This article examines briefly the virtues and vices of an immanent reading of biblical texts. Due to the fact that Jurie le Roux is known as a historical critical scholar, a synchronic methodology is exposed from a diachronic angle. The history and the philosophy underlying a so-called structural analysis are highlighted, the value of this methodology for biblical exegesis is appreciated, nevertheless, it is pointed out that a structural analysis should not mistakenly be regarded as a hermeneutical tool. Furthermore, the theory of the aesthetics of reception of Hans Robert Jauss is dealt with in a very cursory manner as another possible approach toward dealing with biblical texts. However, a critical attitude is called for as it appears that every methodology has its own apparatus that is designed for a particular purpose. Scholars who wish to work in an interdisciplinary way, should do so in a critical and responsible manner.